Development of an In-House Multiplex Nested RT-PCR Method for Detecting Acute HIV-1 Infection in High Risk Populations - Liu, Zhiying; Li, Wei; Xu, Meng; Sheng, Bo; Yang, Zixuan; Jiao, Yanmei; Zhang, Tong; Mou, Danlei; Chen, Dexi; Wu, Hao (Current HIV Research, 2015)
Background: The detection of acute HIV infection (AHI) among high risk populations can help reduce secondary transmission of HIV. The nucleic acid testing (NAT) can shorten the test window period by up to 7-12 days. In this study, we describe an in-house NAT based on the multiplex nested RT-PCR method to detect the HIV RNA. We also evaluated it in a high risk cohort in Beijing. Methods: Four primer pairs were designed and evaluated for the detection of different HIV-1 subtypes in group M. Multiplex RT-PCR and nested PCR were performed. The sensitivity, specialty, primers compatibility among HIV subtypes were evaluated simultaneously. In an MSM cohort in Beijing during a 3-year period, a total of 11,808 blood samples that were negative by ELISA or indeterminate by Western blot were analyzed by this multiplex nested RT-PCR with pooling strategy. Results: The multiplex nested RT-PCR was successfully applied for the detection of at least six HIV-1 subtypes. The sensitivity was 40 copies/ml and the specificity was 100%. A total of 29 people were tested HIV-1 positive with acute infection in a MSM cohort of Beijing during a 3 years period. Conclusion: This multiplex nested RT-PCR provides a useful tool for the rapid detection of acute HIV-1 infection. When used in combination with the 3rd generation ELISA, it can improve the detection rate of HIV infection, especially in the source limited regions.
Keywords: nucleic acid testing (NAT)